Нові місцезнаходження Daphne sophia Kalen. (Thymeleaceae) в Україні - Банік, М.В.; Тверетинова, В.В.; Волкова, Р.Є.; Атемасова, Т.А.; Атемасов, А.А.; Брезгунова, О.О.; Влащенко, А.С.; Гончаров, Г.Л.; Коноваленко, С.В.; Скоробогатов, В.М.; Скоробогатов, Є.В.; Целіщев, О.Г. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2007)
В 2004 г. проведено полное обследование области распространения Daphne sophia Kalen. в Украине благодаря гранту Rufford Small Grants Scheme. Небольшие популяции выявлены только в двух из четырех ранее известных местонахождений вида, причем в одном из них — впервые с 1910 г. Две другие популяции полностью исчезли в связи с террасированием и облесением меловых склонов. Кроме того, в Харьковской обл. обнаружено два новых местонахождения вида. Современный ареал D. sophia в Украине включает четыре местонахождения (три — на правобережье р. Волчья, одно — на правобережье р. Верхняя Двуречная). In 2004 first complete survey of the range of Daphne sophia Kalen. in Ukraine was accomplished with support of Rufford Small Grants Scheme. Among 4 sites where Daphne sophia was historically known in the country only 2 sites still support small populations including one rediscovered for the first time since 1910. Two other populations disappeared completely due to terracing and afforestation of chalk slopes. Moreover, two new locations of the species were discovered in Kharkiv region. Therefore, current distribution of Daphne sophia in Ukraine is confined to 4 sites (3 sites along right bank of Vovcha river and 1 site along right bank of Verchnya Dvorichna river).